Project-level Women's Empowerment in Agriculture Index (pro-WEAI) Foundations Module, a distance learning course developed by A4NH gender researchers - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The distance learning course is designed to train researchers and practitioners on the pro-WEAI tool, from its background to its practical application within the project context.